The Relationship between the Physical Environment of the Home and Parental Behavior with the Incidence of Respiratory Infections in Toddlers in the Working Area of the Hamparan Perak Community Health Center - Elvina; Syafran Arrazy (Universitas Muhammadiyah Palu, 2026)
Background: ISPA is still the leading cause of morbidity and mortality among toddlers, especially in developing countries such as Indonesia. Factors of the physical environment of the home and the behavior of the parents are thought to influence the risk of ARI. Objective: To determine the relationship between the physical environment of the home and the behavior of parents with the incidence of ISPA in toddlers in the working area of the Hamparan Perak Health Center. Methods: A quantitative study with a cross sectional design, involving 122 respondents selected through proportionate stratified random sampling. Data were collected using questionnaires and observations, then analyzed univariate and bivariate using the Chi-Square test. Results: The results of the study proved that there was a significant relationship between ventilation (p=0.036) with PR=2.330 (95%CI=1.121-4.845), floor type (p=0.021) with PR=2.560 (95%CI=1.216-5.388), wall type (p=0.033) with PR=2.384 (95%CI=1.137-4.998), lighting (p=0.032) with PR=2.393 (95%CI=1.142-5.014), humidity (p=0.048) with PR=2.240 (95%CI=1.073-4.675), smoking habits (p=0.024) with PR=2.534 (95%CI=1.192-5.388), and garbage burning habits (p=0.013) with PR=2.744 (95%CI=1.297-5.804) with the incidence of ISPA in toddlers. Meanwhile, occupancy density (p=0.254), temperature (p=0.751), and kitchen ventilation (p=0.116) did not have a significant relationship. Conclusion: The physical condition of the home and the behavior of parents play an important role in the incidence of ISPA in toddlers. Efforts to improve the home environment and control risky behaviors are expected to reduce the incidence of ARI.